A case of stromal sarcoma of the prostate with the incidental detection of prostate adenocarcinoma - Shang Xu; Xinning Wang; Wei Jiao (Urology Case Reports)
Prostate stromal sarcoma is very rare among patients with prostate cancer, accounting for <0.1 % of prostate malignancy. Here, we report a case of prostate stromal sarcoma combined with incidental adenocarcinoma with normal serum PSA after radical prostatectomy. This case is unique in that the occurrence of incidental adenocarcinoma might interfere with the postoperative follow-up and treatment. We can only draw from the experiences of case reports and retrospective analysis. This article describes a presentation of a rare tumor case and a review of the literature.